Financial crisis, legal origin, economic status and multi-bank performance indicators: Evidence from Islamic banks in developing countries. Issue 2 (8th May 2017) - Al-Nasser Mohammed, Sulaiman Abdullah Saif; Joriah Muhammed, Datin
Abstract : Purpose: The purpose of this paper is to investigate the performance of Islamic banks in developing countries from 2007 to 2010 which includes the period of the financial crisis by empirically examining the way in which the macroeconomy affected Islamic banking performance (IBP) in developing countries. The empirical examination involves two approaches of measuring performance: Sharia-based and conventional-based performance measurement. Design/methodology/approach: For this paper, the authors have utilized a Data Stream/Bank Scope database and data from the Bank Negara Malaysia (Malaysian Central Bank) to collect a panel set of annual financial information for Islamic banking from the year 2007-2010. The initial sample covers 34 Islamic banks from developing countries that are listed on the International Islamic Service Board. Furthermore, the authors adopted only those listed Islamic banks to tackle the data availability issue. The authors' final sample comprised 136 observations with complete data as the numbers of Islamic banks in developing countries are low in comparison to their conventional peers. The financial crisis dummy follows America's commonly used National Bureau of Economic Research timeline for the financial crisis. The authors also used the method of a generalized least square (GLS) method of pooled panel data analysis regression model. The rationale for employing the GLS technique was made on the basis of the ability of GLS to give less weight to the error term that is closely clustered around the mean, to improve the goodness of fit and to remove autocorrelation compared with normal, random, and fixed effect models. Findings: The authors of this paper found that the macroeconomic factors reflected in gross domestic product, gross domestic product growth, and inflation rate have a significant positive relationship with the return on assets. In addition, a significant negative relationship was found between the financial dummy and IBP in developing countries. On the other hand, it failed to find evidence of a relationship between the macroeconomic factors and performance including the legal system and the financial crisis dummy, when the performance is reflected by the Zakat ratio. The result embedded that the financial crisis had an impact on the performance of Islamic banks in developing countries when viewed from the conventional banking perspective. The financial crisis played a role in reducing the profitability of Islamic banks which is consistent with a previous study by Hasan and Dridi (2011). However, in the view of Sharia, the financial crisis did not have any effect on IBP; even the macro factors did not have any effect on the level of performance. Research limitations/implications: There are possible explanations for these contradictory coefficient signs. First, the contradictory signs of the coefficient for the same independent variable that was regressed with different dependent variables show that researchers would need to take caution in using the right indicators when measuring IBP. Conventional indicators bring different results in comparison to Islamic indicators (Badreldin, 2009; Mudiarasan. Kuppusamy, 2010; Zahra and Pearce, 1989). Second, Richard et al. (2009), having reviewed performance measurement-related publications in five of the leading management journals (722 articles between 2005 and 2007), suggested that the past studies reveal a multidimensional conceptualization of organizational performance with limited effectiveness of commonly accepted measurement practices. Accordingly, these studies call for more theoretically grounded research and debate for establishing which measures are appropriate in a given research context. Today, there is a general consensus that the old financial measures are still valid and relevant (Yip et al., 2009). However, these need to be balanced with more contemporary, intangible, and externally oriented measures. It has been argued that various researchers working in their own disciplines using functional performance measures (such as market share in marketing, schedule adherence in operations and so on) ought to link their discipline to focused performance measures of overall organizational performance. Practical implications: Islamic banking has unique characteristics in comparison to conventional banking and this paper examines the differences between the two and also investigates the resilience of Islamic banks during a period of economic turbulence. Furthermore, due to these unique characteristics, a comparison cannot be made by using the conventional performance measures alone. In addition, amid the in-depth studies examining the resilience of Islamic banks during periods of economic crises, there are instances of theoretical disagreement in the extant empirical literature examining finance and economics. In that regard, the majority of the existing literature is either based on advanced markets or countries where the majority of the population practices the faith of Islam, and little is known about the performance of Islamic banking from the pooled emerging markets; particularly in developing countries. Originality/value: Introducing Zakat as a performance measurement in Islamic banking context relating it to macroeconomic factors enhances the thinking of new research in Islamic theory about bank performance.